Pengaruh Disiplin Dan Stres Kerja Terhadap Kinerja Karyawan Sfa Resto Karanganyar - Pujiastutik, Titk, Drs. Ma'ruf, MM (2016)
This study aims to determine how much influence the discipline and work stress on employee performance in SFA Resto Karanganyar. This study uses data Primary. The sample in this study using 50 respondents from Resto SFA employees in Karanganyar. Mechanical sampling using sampling rendom ie random sampling technique. Analysis method used is multiple linear regression analysis of simultaneous significance test (Test-F) and a significant test Persia (t-test) and R-square. These results have been through some testing, the validity, reliability test, classic assumption test, berrganda linear regression, t-test, F and determinant coefficient (adjusted R Square). So this study draws conclusions that discipline and work stress memeiliki positive and significant impact on employee performance in SFA Resto Karanganyar. Keywords: Work discipline, Job Stress, Employee Performance